2014
DOI: 10.5888/pcd11.140053
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Receipt of Advice to Quit Smoking From Health Care Providers: 2010 National Health Interview Survey

Abstract: IntroductionNot all smokers receive tobacco cessation advice from health care providers (HCPs) and, although factors associated with receiving HCP advice to quit smoking and the effectiveness of such advice have been examined, no recent study has explored differences between types of HCPs (eg, physicians vs dentists). Our objective was to determine the prevalence of HCP-delivered advice and the characteristics of patients who receive advice to quit smoking from any HCP and, separately, from a physician or a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 11 publications
8
58
2
Order By: Relevance
“…These findings are very similar to those recently released in Australia, which also found a wide discrepancy between acknowledgments of the benefits of smoking cessation and providing active smoking cessation treatment 11 . The lack of knowledge and formal training was compounded by a number of additional perceived barriers to recommending treatment including a lack of time, resources, and perceived importance of quitting smoking.…”
Section: References Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings are very similar to those recently released in Australia, which also found a wide discrepancy between acknowledgments of the benefits of smoking cessation and providing active smoking cessation treatment 11 . The lack of knowledge and formal training was compounded by a number of additional perceived barriers to recommending treatment including a lack of time, resources, and perceived importance of quitting smoking.…”
Section: References Discussionsupporting
confidence: 88%
“…This figure is even lower than that reported recently, which indicated that 11% of smokers receive cessation information from their dentists 11 . In the USA, where smoking cessation services in dental practices are much more established, the rate of referral to specialist services and/or offering cessation prescriptions can be as high as 35% 12 .…”
Section: References Discussioncontrasting
confidence: 59%
“…Not surprisingly, being uninsured was related to smoking among both female and male survivors and controls. In the general population, the uninsured are significantly less likely to receive smoking cessation counseling from a physician, but this issue has not been studied explicitly among AYA survivors [23]. Moreover, similar to the general population [23], healthcare providers may be missing key opportunities to provide smoking cessation counseling to AYA cancer survivors [24] due to lack of time and focus on managing other health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, the uninsured are significantly less likely to receive smoking cessation counseling from a physician, but this issue has not been studied explicitly among AYA survivors [23]. Moreover, similar to the general population [23], healthcare providers may be missing key opportunities to provide smoking cessation counseling to AYA cancer survivors [24] due to lack of time and focus on managing other health conditions. The Patient Protection and Affordable Care Act includes smoking cessation counseling as an essential preventive service [25], meaning that survivors who are in need of smoking cessation services can potentially benefit from this new coverage.…”
Section: Discussionmentioning
confidence: 99%
“…National data from 2010 showed lower smoker counseling rates among Latinos than among non-Latino whites (34). African Americans report lower use of pharmacotherapy and greater skepticism toward those types of medications (121).…”
Section: Preventive Carementioning
confidence: 99%